Penerapan Proses Transformasi Dalam Kegiatan Produksi Untuk Memaksimalkan Laba Pada PT. MIROTA KSM - Yusi Irensi Seppa (Indonesian Journal of Taxation and Accounting, 2023)
A series of company production activities to be able to produce quality products through the process of transforming input into output is important to receive good attention, handling and control from the company so that it can provide the best benefits and the resulting company profits can also be maximized so that it can benefit the company. This research aims to find out how to implement the transformation process in production activities to maximize profits at PT. Mirota KSM. The type of research used is qualitative with a descriptive approach. Data collection techniques include semi-structured interviews and observations as well as visiting companies directly. The research results show that the process of transforming input into output in the manufacture of dairy products such as Lactona in principle goes through 3 stages, namely the preparation stage, the mixing stage and the packaging stage. The transformation process combines input or company resources to support the creation of production output. Good quality products produced from a series of production processes will increase product demand so that sales increase and company profits are maximized and can benefit the company.